The Effect of A Dietary Selection Promotion Program on Blood Pressure Among Hypertensive Inmates: A District Prison in the Upper Southern Region - Chaitokate, Nampung; Noonil, Naiyana; Akewarangkoon, Saifon; Songprasert, Thanawan (Science, Technology, and Social Sciences Procedia, 2025)
Hypertension is a prevalent health issue among incarcerated populations and is closely linked to poor dietary habits. Despite existing prison healthcare services, many inmates continue to engage in unhealthy food consumption, particularly through welfare shop purchases. Quasi-experimental study aimed to investigate the impact of a dietary selection promotion program on blood pressure levels among hypertensive inmates in a district prison in the upper southern region of Thailand. A 12-week intervention was implemented among 78 incarcerated individuals with hypertension, randomly assigned to experimental and control groups (39 participants each). The program was based on the Health Belief Model (HBM) and included group education, experience sharing, and a peer-supported “buddy system”. Data were collected using questionnaires, food frequency records, and blood pressure monitoring. Statistical analyses included Chi-square, Fisher’s exact test, paired t-tests, and independent t-tests. The study found that participants were predominantly male (82.1%) with a mean age of 46.28 years (SD = 9.29). Post-intervention, the experimental group showed a significant reduction in both systolic (132.79 ± 9.41 to 123.49 ± 11.08 mmHg) and diastolic (86.44 ± 7.76 to 77.23 ± 8.10 mmHg) blood pressure (p < 0.05). Furthermore, their post-intervention blood pressure levels were significantly lower than those in the control group (systolic: 123.49 ± 11.08 vs. 137.56 ± 14.54 mmHg; diastolic: 77.23 ± 8.10 vs. 89.87 ± 9.16 mmHg, p < 0.05). Thus, the dietary selection promotion program effectively reduced blood pressure among hypertensive inmates by fostering informed food choices and peer support. Integrating such interventions into routine prison healthcare may enhance chronic disease management and reduce hypertension-related complications.